2020
DOI: 10.1088/1757-899x/722/1/012037
|View full text |Cite
|
Sign up to set email alerts
|

Innovativeness, Proactiveness, and Risk-taking: Corporate Entrepreneurship of Indonesian SMEs

Abstract: Corporate entrepreneurship (CE) consists of three dimensions, which are innovativeness, proactiveness, and risk-taking. It has an essential role in ensuring SMEs willingness to adopt technology in the 4.0 industrial era. The aim of this study is twofold. First, to discover the pattern CE (innovativeness, proactiveness, and risk-taking) intensity on four SMEs and second, to identify the likely causes of that pattern from a strategic management perspective. This research employed a case study design with four In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 42 publications
1
11
0
1
Order By: Relevance
“…This can also be defined as the transfer of resources to projects of high uncertainty (Karacaoglu et al, 2013). Kolaković, et al, (2008) also highlighted that risk taking has a significant association with corporate entrepreneurship which might be observed repeatedly while examining the literature on corporate entrepreneurship (Ketchen & Short, 2012).In actuality this makes the firm to be involved in bold actions rather than cautious actions (Ketchen & Short, 2012), and became an integral part of corporate entrepreneurship as the business environment is dynamic and unstable and companies have to take risk in order to sustain and to retain their market share (Astrini, 2020). Although the study of Morris and Kuratko (2002) indicated that corporate entrepreneurship in the public sector significantly lacks risk taking in comparison to innovation and proactiveness.…”
Section: Proactivenessmentioning
confidence: 93%
See 3 more Smart Citations
“…This can also be defined as the transfer of resources to projects of high uncertainty (Karacaoglu et al, 2013). Kolaković, et al, (2008) also highlighted that risk taking has a significant association with corporate entrepreneurship which might be observed repeatedly while examining the literature on corporate entrepreneurship (Ketchen & Short, 2012).In actuality this makes the firm to be involved in bold actions rather than cautious actions (Ketchen & Short, 2012), and became an integral part of corporate entrepreneurship as the business environment is dynamic and unstable and companies have to take risk in order to sustain and to retain their market share (Astrini, 2020). Although the study of Morris and Kuratko (2002) indicated that corporate entrepreneurship in the public sector significantly lacks risk taking in comparison to innovation and proactiveness.…”
Section: Proactivenessmentioning
confidence: 93%
“…Therefore, an organization may implement innovation by applying new organizational structures, designing new services, and optimizing organizational work process (Currie, Humphreys, Ucbasaran & McManus, 2008). Thus, innovation is the characteristic which may lead to competitive edge (Ahmed et al, 2011), & concern towards this might be measured through investment in R&D and introducing new products (Astrini et al, 2020). However, in public sector, innovation is majorly concerned with designing and implementation of new processes, rather than other components (Diefenbach, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…As indicated by Centobelli et al (2019), innovativeness is a key indicator for the financial and non-financial success of SMEs. Further, risk-taking is important in improving the organisational efficiency (Jung et al, 2020), as proven for SMEs (Astrini et al, 2020;Games, 2019). Pro-activeness improves financial efficiency (Hossain & Al Asheq, 2019) and has an important influence on SMEs (Jalali et al, 2013).…”
Section: Entrepreneurial Orientation and Smes Performancementioning
confidence: 99%